CHALLENGES OF LEARNING ENGLISH AS A SECOND LANGUAGE (ESL) (Web of Teachers: Inderscience Research, 2026)
Learning English as a Second Language (ESL) is a complex, multifaceted process influenced by linguistic, psychological, and socio-cultural factors. This article examines the primary challenges faced by ESL learners, ranging from phonological hurdles and grammatical nuances to sociocultural barriers. Through a synthesis of existing literature and qualitative observation, the study identifies that while cognitive aptitude plays a role, environmental support and emotional resilience are the primary determinants of success. The findings suggest that a holistic approach to pedagogy, focusing on communicative competence rather than rote memorization, is essential for overcoming these barriers.